Botanical, agronomic, phytochemical and biological characteristics of Aspidosperma pyrifolium Mart.: A review (Research, Society and Development, 2020)
Known in popular medicine as “pereiro”, Aspidosperma pyrifolium has economic importance due to the use of its wood. However, there are no studies that provide relevant information related to botanical, agronomic, phytochemical and biological characteristics involving this plant species. Given the above, this study aimed to develop a study on different characteristics of A. pyrifolium. The present study is a narrative bibliographic review. Articles, monographs, dissertations and theses retrieved from the following databases were included: Lilacs, Scielo, PubMed, ScienceDirect and Banks of Theses and Dissertations from Public Universities. The studies highlight the use of A. pyrifolium by several populations, especially in the Northeast region of Brazil, more precisely in the Caatinga biome, where it has economic and ecological importance. Regarding metabolites, the presence of flavonoids and alkaloids is mainly observed. In addition, studies also report that this plant has analgesic, anti-inflammatory action, combats ectoparasites and infections, improves erectile dysfunction and has hypotensive activity. On the other hand, toxicity has been reported in different animal models. Thus, it is observed that “pereiro” has the potential to become a possible drug, phytodrug and/or phytotherapic.